MODELLING A 1-DOF FINGER EXTENSOR MACHINE FOR HAND REHABILITATION - Shahdad, Ifrah; Azlan, Norsinnira Zainul; Jazlan, Ahmad (IIUM Engineering Journal, 2021)
It is essential to have an accurate representation of a robotic rehabilitation device in the form of a system model in order to design a robust controller for it. This paper presents mathematical modelling and validation through simulation and experimentation of the 1-DOF Finger Extensor rehabilitation machine. The machine’s design is based on an iris mechanism, built specifically for training open and close movements of the hand. The goal of this research is to provide an accurate model for the Finger Extensor by taking into consideration various factors affecting its dynamics and to present an experimental validation of the devised model. Dynamic system modelling of the machine is performed using Lagrangian formulation and the involved physical parameters are obtained experimentally. To validate the developed model and demonstrate its effectiveness, hardware-in-the-loop experiments are conducted in the Simulink-MATLAB environment. Mean absolute error between the simulated and experimental response is 1.38° and the relative error is 1.13%. The results obtained are found to be within the human motion resolution limits of 5 mm or 5º and exhibit suitability of the model for application in robotic rehabilitation systems. The model accurately replicates the actual behavior of the machine and is suitable for use in controller design. ABSTRAK: Gambaran tepat mengenai model sistem peranti rehabilitasi robotik adalah sangat penting bagi pembangunan sesebuah reka bentuk alat kawalan tahan lasak. Kajian mengenai model matematik dan pengesahan melalui simulasi dan eksperimentasi mesin pemulihan 1-DOF ‘Finger Extensor’. Mesin ini direka bentuk berdasarkan mekanisme iris, dibangunkan khusus bagi melatih gerakan buka dan tutup tangan. Tujuan kajian ini adalah bagi menyediakan model Finger Extensor yang tepat dengan mengambil kira faktor mempengaruhi dinamik dan pengesahan model eksperimen yang dirancang. Model sistem dinamik mesin ini diuji menggunakan formula Lagrangian dan parameter fizikal yang terlibat diperoleh melalui eksperimen. Model ini disahkan dan diuji keberkesanannya menggunakan eksperimen Perkakasan-dalam-gelung melalui MATLAB-Simulink. Purata ralat mutlak antara dapatan simulasi dan respon eksperimen adalah 1.38° dan ralat relatif 1.13%. Dapatan kajian adalah dalam had resolusi gerakan tangan manusia iaitu 5 mm atau 5º dan didapati model ini sesuai bagi aplikasi sistem rehabilitasi robotik. Model ini tepat dalam mereplikasi kelakuan sebenar mesin dan sesuai digunakan bagi reka bentuk kawalan.